(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article focuses on the studying impersonal sentences in Azerbaijani and English languages. It also investigates differences of sentence structure in these two languages. The author represents various linguists’ thoughts and gives examples of impersonal sentences in both languages.